Model Implementasi Artificial Intelligence Dalam Produksi Media Pada Lembaga Publik: Studi Komparatif TVRI Yogyakarta dan Dinas Komunikasi Informatika dan Persandian Kota Yogyakarta - Dina Dwika Oktora; Diana Khuntari; Dhety Chusumastuti (eScience Humanity Journal, 2026)
This study aims to analyze and compare the implementation of Artificial Intelligence (AI) in media production processes within public institutions, namely TVRI Yogyakarta and the Department of Communication, Informatics, and Encryption of Yogyakarta City. The research employed a qualitative approach using a comparative case study design. Data were obtained from previous studies conducted at both institutions through interviews, observations, and documentation. The findings reveal that AI has been utilized in various stages of media production, including scriptwriting, content ideation, music generation, audiovisual editing, media monitoring, and digital public services. TVRI Yogyakarta primarily uses AI to support script development, music creation, and visual enhancement for non-news programs. Meanwhile, Diskominfo Yogyakarta applies AI more broadly in content production, issue monitoring, content management, editing, and chatbot-based public services. Both institutions experience similar benefits, including improved efficiency, accelerated production processes, and increased innovation opportunities. However, challenges remain, such as limited human resource competencies, concerns regarding data accuracy, ethical considerations, and the absence of comprehensive governance frameworks. The comparative analysis indicates that AI adoption in both institutions remains at the augmentation stage, where AI serves as a supporting tool rather than replacing human creativity and decision-making. This study contributes to the understanding of AI-driven digital transformation in public media institutions and proposes a conceptual model for AI-assisted media production in the public sector.